Evaluation of Strain Distribution in Bone around Implant in Treatment Design of Overdentures Using Computer and Modeling of Finite Elements - Masoumeh Khoshhal; Fariborz Vafaee; Sahar Raisi (Mashhad University of Medical Sciences, 2016)
Introduction: Introduction: Few studies have investigated the distribution of stress around implants. In this study the distribution of stress in bones around implants was investigated in five overdenture (OD) treatment designs including OD-1, OD-2, OD-3, OD-4 and OD-5. Materials and methods: The Catia modeling software was used in order to simulate the tooth/implant model and bone. First, the borders of cancellous and cortical bone in each section of the CT images were attained by Photoshop software. Then, modeling softwares SolidWorks and NUMBER were applied to make the final three-dimensional model of jaw. Finally, the amount of stress on the surface of bone/implant was studied by means of stress analysis software (Ansys v11.0). Results: Protrusive movements of implants B and D in OD-1 showed the highest amount of strain, 2435 εµ. Also, high amounts of strain, 1668 and 1557 εµwere observed in OD-1 and OD-2 designs in lateral movements respectively. Conclusion: The bottom line is that no forces to the extent of destruction based on the Ferost model were found for these designs. The highest amount of strain occurred in OD-1 design, which is held in mild overload window. Moreover, the amounts of strain in the rest of designs investigated were in adaptive window.